Kasus Grup Fantasi Sedarah di Facebook: Analisis Fiqih Jinayah terhadap Kejahatan Seksual Virtual - Naufal Rizky Fadhilah; Yasmin Raihanah Zaviril; Raja Albar Pandapotan Simatupang; Bunga Amalia Nasution; Adrian Seputro Ginting (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The development of digital technology has had a major impact on social interaction patterns, including in terms of deviant sexual behavior in the virtual realm. One case that has emerged is the existence of the